The Ongoing Challenge of Hematopoietic Stem Cell-Based Gene Therapy for β-Thalassemia - Drakopoulou, Ekati (SAGE-Hindawi Access to Research, 2011)
β-thalassemia is characterized by reduced or absence of β-globin production, resulting in anemia. Current therapies include blood transfusion combined with iron chelation. BM transplantation, although curative, is restricted by the matched donor limitation. Gene therapy, on the other hand, is promising, and its success lies primarily on designing efficient globin vectors that can effectively and stably transduce HSCs. The major breakthrough in β-thalassemia gene therapy occurred a decade ago with the development of globin LVs. Since then, researchers focused on designing efficient and safe vectors, which can successfully deliver the therapeutic transgene, demonstrating no insertional mutagenesis. Furthermore, as human HSCs have intrinsic barriers to HIV-1 infection, attention is drawn towards their ex vivo manipulation, aiming to achieve higher yield of genetically modified HSCs. This paper presents the current status of gene therapy for β-thalassemia, its success and limitations, and the novel promising strategies available involving the therapeutic role of HSCs.